Precipitation controls the time-lag and cumulative effects of hydrothermal factors on the end of the growing season in a semi-arid region of China - Liu, Erhua; Zhou, Guangsheng; Lv, Xiaomin; Song, Xingyang (Frontiers in Plant Science, 2024)
Climate change has substantial influences on the end of the growing season (EOS). The time-lag and cumulative effects are non-negligible phenomena when studying the interaction between climate and vegetation. However, the quantification of temporal effects of climatic factors on the EOS in the context of changing hydrothermal patterns remains scarce. Based on the moderate resolution imaging spectroradiometer (MODIS) fraction of absorbed photosynthetically active radiation (FPAR), the study firstly inverted the EOS of typical steppe vegetation in a semi-arid region of China, and then quantified the time-lag and cumulative effects of monthly total precipitation (PRE) and monthly average temperature (TEM) on the EOS during 2003–2022. A turning point occurred in 2011; the EOS displayed an advancing trend until 2011, followed by a delayed trend. Accordingly, the climatic background changed from warming and drying conditions during 2003–2011 to warming and wetting conditions during 2011–2022. The time-lag scales of PRE and TEM on the EOS decreased from 2- and 4-month scales during 2003–2011, respectively, to 1- and 2-month scales during 2011–2022, respectively. The time-lag degree of hydrothermal factors on the EOS weakened with increased precipitation. The cumulative time scales of the EOS response to PRE and TEM were mainly concentrated within 1-month during different time periods, but the EOS was more sensitive to short-term precipitation. The time-lag and cumulative partial correlation coefficient of PRE to the EOS changed from mainly negative regulation during 2003–2011 (39.2, and 50.0%, respectively) to mainly positive regulation during 2011–2022 (67.8, and 93.7%, respectively). The time-lag and cumulative effects of TEM on the EOS were positive with the precipitation and temperature gradient under the warming and wetting climate, which indicated that increased precipitation was a prerequisite for temperature to induce a delayed EOS in the semi-arid study region. This study emphasizes the important role of precipitation in regulating the EOS response to hydrothermal factors in semi-arid regions.